\(x^2+\frac{4x^2}{\left(x-2\right)^2}=12\)

">
K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

9 tháng 6 2016

\(\Leftrightarrow\left[x^2+\left(\frac{2x}{x-2}\right)^2+2.x.\frac{2x}{x-2}\right]-\frac{4x^2}{x-2}=12\)

\(\Leftrightarrow\left(x+\frac{2x}{x-2}\right)^2-\frac{4x^2}{x-2}-12=0\)

\(\Leftrightarrow\left(\frac{x^2}{x-2}\right)^2-4.\frac{x^2}{x-2}-12=0\)

9 tháng 6 2016

\(\Leftrightarrow\frac{4x^2}{x^2-4x+4}+x^2-12=0\)

\(\Leftrightarrow\frac{x^4-4x^3-4x^2+48x-48}{x^2-4x+4}=0\)

\(\Leftrightarrow x^4-4x^3-4x^2+48x-48=0\)

\(\Leftrightarrow x^2+2x-4=0\)

\(\Leftrightarrow\orbr{\begin{cases}x=-\sqrt{5}-1\\x=\sqrt{5}-1\end{cases}}\)

NV
22 tháng 2 2020

ĐKXĐ: ...

\(\Leftrightarrow\frac{2\left(x^2+1\right)}{\left(1-x^2\right)^2}+\frac{1}{4x^2}=\frac{\left(3x^2+1\right)^2}{144}\)

Đặt \(\left\{{}\begin{matrix}1-x^2=a\\4x^2=b\end{matrix}\right.\)

\(\Rightarrow\frac{2a+b}{a^2}+\frac{1}{b}=\frac{\left(a+b\right)^2}{144}\)

\(\Leftrightarrow\frac{\left(a+b\right)^2}{a^2b}=\frac{\left(a+b\right)^2}{144}\)

\(\Leftrightarrow\left[{}\begin{matrix}a+b=0\left(vn\right)\\a^2b=144\end{matrix}\right.\)

\(\Leftrightarrow\left(1-x^2\right)^2.4x^2=144\)

\(\Leftrightarrow\left(2x-2x^3\right)^2=12^2\)

\(\Leftrightarrow...\)

12 tháng 5 2018

a,-0,162

23 tháng 11 2022

a: =>(x^2+4x-5)(x^2+4x-21)=297

=>(x^2+4x)^2-26(x^2+4x)+105-297=0

=>x^2+4x=32 hoặc x^2+4x=-6(loại)

=>x^2+4x-32=0

=>(x+8)(x-4)=0

=>x=4 hoặc x=-8

b: =>(x^2-x-3)(x^2+x-4)=0

hay \(x\in\left\{\dfrac{1+\sqrt{13}}{2};\dfrac{1-\sqrt{13}}{2};\dfrac{-1+\sqrt{17}}{2};\dfrac{-1-\sqrt{17}}{2}\right\}\)

c: =>(x-1)(x+2)(x^2-6x-2)=0

hay \(x\in\left\{1;-2;3+\sqrt{11};3-\sqrt{11}\right\}\)

1 tháng 8 2017

b)  \(\frac{2\left(x+1\right)}{3x^2+x}+\frac{13\left(x+1\right)}{3x^2+x+6\left(x+1\right)}=6\)  (1)

Đặt  \(a=x+1;b=3x^2+x\)  thì

\(\left(1\right)\Leftrightarrow\frac{2a}{b}+\frac{13a}{b+6a}=6\)

\(\Leftrightarrow4a^2-7ab-2b^2=0\)

\(\Leftrightarrow\left(a-2b\right)\left(4a+b\right)=0\)

\(\Leftrightarrow\orbr{\begin{cases}a=2b\\a=-\frac{1}{4}b\end{cases}}\)

Đến đây thì dễ rồi